Tatak Pilipino [episode no. 35]. ([Quezon City ABS-CBN, 1991)
A unique display of Pilipino ways and style.
Sex letter sending (20 min.) -- Apung Juan C. Flores (10 min.) -- Bakya - wooden slippers (5 min.) -- Aswang (15 min.) -- Caltex feature for Science and Technology (10 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Flores, Juan C; Footwear -- Philippines; Inventions -- Philippines; Vampires; Media and sex -- Philippines